A Monetary Union in Asia? Some European Lessons - Wyplosz Charles (East Asian Economic Review, 2001)
Monetary Union in Europe has been the natural response to the combined desire of stabilizing intra-European exchange rates and of lifting permanently all capital controls. The commitment to stable exchange rate has long been rooted in policymakers’ conviction that trade integration requires precise rules which eliminate the risk of misalignments, whether imposed by the markets or arranged by the authorities. The success in maintaining fixed-but-adjustable exchange rates within the EMS and next in adopting a single currency is largely due to the patient and progressive building institutions that became the uneasy repository of those parts of national sovereignty that have been abandoned. This experience suggests three lessons for current discussions about a monetary union in Asia. First, multilateral regional exchange rate arrangements are more conducive to an effective defense than indirect approaches like basket pegs. They probably require some limits to capital mobility. Second, adopting a single currency necessitates elaborate preparations that can only be underpinned by the gradual build up of collective institutions. Third, a monetary union requires some reasonable degree of real convergence. This implies starting with a core of sufficiently homogeneous countries. At this stage, starting with a monetary union in Asia would imply reversing the European sequencing, which started with a common market, moved on to the EMS, and liberalization of capital movements.